Stranger in A Strange Land: Is Indonesia’s Limited Dual Citizenship Policy Antiquated? - Nur Gemilang Mahardhika (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The United Nations identified them as part of the “international migrants” movement; they call themselves the “Indonesian Diaspora” – a lingering name to which the public’s ears have become rather acquainted with. Born in 2012, the Diaspora crusade vined through all odds that one specific Presidential Regulation on their account was enacted in 2017. The Regulation defines the composition of Indonesian Diaspora to include not only Indonesian nationals living abroad but also ‘foreigners’ who once bore the Indonesian citizenship status as well as the descendants of these two groups. Nonetheless, on one certain matter, both international communities as represented by the UN and the Diaspora itself appear to share a common belief: that the international migrations contribute greatly in national development and economic growth of the migrants’ origin country. However, such contributions are also believed to have not been requited by sufficient support from the origin country (in this case, Indonesia) or at the very least, by ease of administrative affairs in the running of their lives. Over the seas, these Indonesians face challenges for being Indonesians, instead of bearing the citizenship status of their residing country – even when they have pocketed the (permanent) resident’s permit; while on the Indonesian soil, they face hardship for being away too long that they have to forfeit their Indonesian ID card. Although releasing the Indonesian citizenship status and embracing that of their habitual residence might seem like one of, if not the only, viable options, one just simply cannot cut the cord that connects them to their Motherland. For some, returning home a stranger is too great an ache to bear. To ease the pain, Indonesian Government conjured a Limited Dual Citizenship policy granted to the children of mixed marriage between an Indonesian parent and their foreigner spouse. An immigration service in the form of affidavit is also given from this scheme. The system has worked for quite some time, until further difficulties arise. Now the Indonesian Diaspora has once again pleaded for actual dual citizenship instead of limited one. Hence, this writing serves as a response to the plea. The discussion explores whether Indonesian policy on Limited Dual Citizenship has reached its due and most importantly, addresses whether national defence and security issues really have become an outdated rationale to oppose the long-desired notion. This writing is wrapped by comparing circumstances surrounding Indonesia with two states: one that adopts the dual citizenship policy, being Australia; and one that firmly rejects it, being Japan.